Satire, Comedy and Tragedy: Sterne’s “Handles" to Tristram Shandy - Raymond, Richard C (Anthem Press, 2023)
This book provides a closereading of the satiric, comic, and tragic plot structures of TristramShandy and then traces the themes that inform Laurence Sterne's greatest novel to his letters, sermons, and other writings. The book also argues for a writing-to-learn approach to teaching Sterne's recurring themes.